XPS and ESR study of tantalum nanoparticles - Shpak, A.P.; Korduban, A.M.; Trachevsky, V.V. (Functional Materials, 2004)
The electron structure of the films formed by ensemble of tantalum nanoparticles has been studied using XPS and EPR methods. Spectra of internal atomic levels of the film surface have been obtained using step-by-step annealing in vacuum. Using Ta4f spectra decomposition into components, the kinetics of phase formation processes has been investigated.